Respuestas

2013-08-09T02:31:21+02:00
                                               
                                                                                 
     3x + 2y +  z =   4                        3x + 2y +  z =   4
     2x -  3y + 2z =  -7                       -2x + 3y - 2z =   7   multiplicando por -1
       x + 4y  -   z = 10                        - x -  4y + z = -10   multiplicando por -1
                                                                       y = 1
    reemplazando  el valor de y en las dos primeras ecuaciones tenemos:
     3x + 2(1) +  z =   4         3x + 2 +  z =  4          3x +   z =  2
     2x -  3(1) + 2z = -7          2x - 3 + 2z = -7          2x + 2z = -4 

                                                                          -6x -  2z = -4   multiplicando por -2
                                                                           2x + 2z = -4
                                                                                  -4x = -8
                                                                                     x = 2
                                                               entonces         z = -4